Transformational leadership behaviours as the predictor of teachers' job satisfaction : a study at selected secondary public schools in Namangan, Uzbekistan - Abdukhamidovna, Sadokat Karimova (Kulliyyah of Education, International Islamic University Malaysia, 2017)
The purpose of this study is to investigate transformational leadership behaviours as the predictor of teachers' job satisfaction at selected secondary public schools in Namangan, Uzbekistan. The study also investigates the level of principals' transformational leadership practices and teachers' job satisfaction, the predictive ability of transformational leadership behaviours on teachers' job satisfaction, differences in the job satisfaction among teachers of different: gender, degree of education, age and year of experience and also the relationship between transformational leadership practices and teachers' job satisfaction at selected secondary public schools in Namangan. To achieve these purposes, the study employs a questionnaire using 4-point Likert scale for collecting data from the teachers who have minimum two years of teaching experience at selected schools. The collected data is analysed by using a number of statistical tools: descriptive analysis, independent sample t-test, linear regression, one way ANOVA and Pearson's correlation. The sample of the study is selected through employing a stratified sampling method. The respondents are 125 teachers from four selected secondary public schools in Namangan. The results indicate that respondent teachers perceive the level of their principals' transformational leadership practices as moderate. The teachers also indicate the level of their job satisfaction to be moderate at selected secondary public schools. The findings reveal that transformational leadership behaviours highly predict teachers' job satisfaction. Furthermore, a significant difference is found between male and female teachers regarding to their job satisfaction. However, the results do not indicate any differences in teachers' job satisfaction regarding to their degree of education, age and year of experience. According to the findings, positive and strong relationship is found between principals' transformational leadership behaviours and teachers' job satisfaction. Based on the findings, the study presents implications, some recommendations for secondary public schools on how to increase teachers' job satisfaction, and suggestions for future research in this area.